From trauma to depression: structural, synaptic, epigenetic, and molecular pathways linking early stress to lifelong vulnerability - Takahashi, Mina; Shelton, Richard C. (Frontiers in Psychiatry, 2025)
Major depressive disorder (MDD) is a complex and debilitating condition with high global prevalence. While pharmacological treatments are available, the long-term biological underpinnings – especially those linked to adverse childhood experiences (ACEs), remain incompletely understood. ACEs, including physical, sexual, and emotional abuse, neglect, and other traumas, significantly increase lifelong vulnerability to depression and reduce responsive to treatment. Epigenetic mechanisms such as DNA methylation and altered expression of mRNA and short and long non-coding RNAs such as microRNAs (miRNAs) are emerging as key mediators of the relationship between early environmental adversity and brain development and function. Specific miRNAs (e.g., miR-124, miR-135) influence neuroinflammation, and affect synaptic plasticity and monoaminergic signaling. Concurrently, DNA methylation in promoter regions can silence genes critical for stress regulation. For example, hypermethylation of the NR3C1 gene (encoding the glucocorticoid receptor) has been linked with altered HPA axis feedback and cortisol imbalance following ACEs. These epigenetic changes, together with trauma-induced microglial activation and neuroinflammation, may create lasting neural vulnerability. This paper explores how the interplay between childhood trauma, hormonal dysregulation, microglial activation, and epigenetic modification contributes to the pathophysiology of depression. Synthesizing evidence across epigenetic networks and neurobiological systems can deepen an understanding of trauma-related mood disorders. This may inform targeted interventions, identify biomarkers for diagnosis and treatment, and support personalized approaches to care and suicide prevention.